Front Cover: Creation of Highly Dispersed Supported Polyoxometalate Cesium Salts via Cation Exchange from Alkylammonium Salts on Supports (ChemNanoMat 2/2023). Issue 2 (23rd January 2023) - Suzuki, Takaaki; Yabe, Tomohiro; Wachi, Keiju; Yonesato, Kentaro; Suzuki, Kosuke; Yamaguchi, Kazuya
Abstract : A new method was developed for preparing highly dispersed supported polyoxometalate Cs salts that maintain the original Keggin structure after cation exchange of the corresponding supported polyoxometalates tetra‐ n ‐butylammonium salts. This method successfully provided thermal stability to the supported polyoxometalates and can be applied to various supports. These materials can potentially achieve challenging gas‐phase reactions, such as selective oxidation of methane. More information can be found in the Research Article by Kazuya Yamaguchi, Tomohiro Yabe et al.